Genetic causes of transitions from sexual reproduction to asexuality in plants and animals. (26th March 2014) - Neiman, M.; Sharbel, T. F.; Schwander, T.
Abstract The persistence of sexual reproduction in the face of competition from asexual invaders is more likely if asexual lineages are produced infrequently or have low fitness. The generation rate and success of new asexual lineages will be influenced by the proximate mechanisms underlying transitions to asexuality. As such, characterization of these mechanisms can help explain the distribution of reproductive modes among natural populations. Here, we synthesize the literature addressing proximate causes of transitions from sexual to asexual reproduction in plants and animals. In cyclical and facultatively asexual taxa, individual mutations can cause obligate asexuality. The evolution of asexuality in obligately sexual groups is more complex, requiring the simultaneous acquisition of two traits generally controlled by different genetic factors: unreduced gamete formation and spontaneous development of unfertilized gametes. At least three 'pre‐adaptations' could favour transitions to obligate asexuality in obligate sexuals. First, linkage among loci affecting separate key components of asexuality facilitates its spread, with evidence for these linkage blocks in plants. Second, asexuality should evolve more readily in haplodiploids; support for this hypothesis comes from two examples where a single locus causes transitions to asexuality. Third, standing genetic variation for the production of unreduced gametes could facilitate transitions to asexuality, but whether the ability to produce unreduced gametes contributes to the evolution of obligate asexuality remains unclear. We close by reviewing the associations between asexuality, hybridization and polyploidy, and argue that current data suggest that hybridization is more likely to play a causal role in transitions to asexuality than polyploidy.